Implementasi Kebijakan Rehabilitasi Sosial Rumah Tidak Layak Huni (RUTILAHU): Studi Kasus di Kelurahan Made Kota Surabaya - Chrisanty, Rachel Zefanya; Manggalou, Singgih (IAI Nasional Laa Roiba Bogor, 2024)
The Indonesian Government has created a policy on Social Rehabilitation of Uninhabitable Houses to overcome poverty in urban communities. This policy is based on the condition of community home ownership, which is classified into uninhabitable housing conditions. Therefore, houses that are uninhabitable must be built according to government decisions in the process of implementing the Social Rehabilitation of Uninhabitable Houses policy. This study aims to identify the process and implementation of the Social Rehabilitation Policy for Uninhabitable Houses (RUTILAHU) in Made Village, Surabaya City, using the theory of George C. Edward III. Descriptive qualitative research methods are employed to objectively describe the reality of the events under study. This study found that the implementation of the policy has been successful overall, but not yet complete. While targets have not been met, the development process must continue because there are still 13 poor families out of 20 families proposed by the Musrenbangkel results in the Rutilahu priority list whose house construction has not been realised.